(untitled) (Proceedings of The National Conference on Community Engagement, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in Dermo Village, particularly in the batik sector, have great potential for economic progress, but there are obstacles in terms of marketing, which tends to be conventional. This Thematic Real Work Lecture (KKN-T) program aims to optimise the marketing of MSME products through the digitisation of creative content and the use of e-commerce platforms. The implementation method is carried out systematically through stages of socialization, surveys and problem identification, creation and optimization of digital accounts (social media and marketplaces), production of creative content, product publication, technical guidance, to mentoring and evaluation. The results of the activity show an increase in the visibility and competitiveness of Dermo Village batik products through the formation of Dermo Shop as a digital showcase, the availability of informative and attractive promotional content, and increased understanding among SME actors in managing digital-based marketing. This program has a positive impact on strengthening the branding of local products and serves as a strategic step in supporting sustainable community economic empowerment in the digital era.